DNA Entrepreneurship Building Melalui Pendidikan Islam (Kajian Tafsir Tematik Perspektif Tafsir al-Mishbah Karya M. Quraish Shihab) - Sarwadi Sulisno; Danang Dwi Prasetyo (SALIHA: Jurnal Pendidikan & Agama Islam, 2022)
Man since the beginning of creation has been equipped with the potential to support his life.  The tendency of humans to love property and vehicles is the first signal of DNA to survive in every generation.  As mentioned in the interpretation of al mishbah that the potential that is taukifily given to man is the grace of loving the shah of the treasury and the purpose of creation as a caliph. It is this wedge between the love or tendency to defend oneself and the mission of the caliph that becomes the Gen entrepreneurship.  Therefore in Education this gene must get a touch through Islamic Education so that the fitrah entreprneurship remains in accordance with the desired of the purpose of human creation. This research is a literature research with a maudhu'I interpretation approach with the subject of research on the interpretation of al mishbah by M. Quraish Shihab. Researchers are trying to explore the DNA of human entrepenuership potential through a thematic interpretation approach as well as how to build it into a skill through Islamic Education. The results of the study prove that humans since the default have been equipped with the potential for entrepreneurship or DNA to queueprneurship.